The Role of PET/CT to Detect Bone Marrow Involvement in Hodgkin Lymphoma - (:unkn) unknown (BEZMIALEM VAKIF UNIV, 2019)
Objective: Bone marrow involvement (BMI) is a significant component of staging of Hodgkin's lymphoma (HL). Unilateral bone marrow biopsy (BMB) from dorsal iliac bone is the standard method to determine BMI. Positron emission tomography/computerized tomography (PET/CT) is recommended as a complimentary technique to determine BMI and to evaluate response to treatment. The aim of this study is to determine whether PET/CT can replace BMB to detect BMI in patients with HL. Methods: A total of 159 patients diagnosed as having HL were evaluated retrospectively. One hundred and four patients who met the criteria were included in the study. BMB and PET/CT were performed on all patients during initial staging. Results: Of the 104 patients, 44 (42.3%) and 17 (16.3%) had BMI in PET/CT and BMB respectively. All patients who had BMI in BMB also had involvement in PET/CT. BMB did not detect BMI in 27 patients who had BMI in PET/CT. All 27 patients had partial or complete remission on PET/CT performed at the end of treatment. This finding was regarded as a relative indicator for BMI. PET/CT had a sensitivity and negative predictive value of 100%, specificity of 68.9% and accuracy rate of 74% to determine BMI. Conclusion: We observed that PET/CT and BMB were compatible to determine BMI in patients diagnosed with HL. Unilateral BMB may result false negative especially in cases with focal involvement. Therefore, PET/CT should be considered as a complimentary technique to determine BMI. Staging should be reevaluated in patients who have BMI in PET/CT and a negative BMB treatment should be planned accordingly.
Keywords: Hodgkin's lymphoma; positron emission tomography; bone marrow biopsy; bone marrow involvement